The collaborative-dialogical dimension in the pedagogical work of the soccer teacher/La dimensión colaborativa-dialógica en la labor pedagógica del profesor de fútbol - Rosa Elvira Cabrera Acosta; Alina Bestard Revilla; Carlos Roberto Sierra Barbado (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
Introduction: Dialogic communication skills are a necessity for the good performance of the pedagogical work of the sports teacher. However, the little use of tools that place the student-athlete as a subject of their own learning process is still a problem. Objective: It consisted of developing a training procedure focused on communication to treat the relationships established between teacher and student-athlete during the process of teaching the sport of soccer in the 11-12-year-old school category of District #4. " Abel Santamaría" Santiago de Cuba. Materials and methods: From the diagnosis made to ten teachers of the male soccer team of the selected center, it was possible to verify the deficiencies in the assumption of developing, reflective and creative procedures for teaching the contents of sport. To carry out this study, methods such as: observation, survey and interview were applied, as well as the Linkert rating scale to assess the degree of acceptance and applicability of the proposal. Results: A training instrument was obtained for the improvement of the collaborative-dialogical dimension of the soccer teacher in the subject-subject-object interrelation, based on main studies of authors, which made it possible to strengthen the pedagogical work in the acting subjects of the process and, consequently, the gradual transformation in the mode of pedagogical professional performance of the soccer teacher during the teaching-learning process. Conclusions: The results of the application emphasize the need to express assertive communication reflected in a continuous process of denials and meanings in the objective behavioral orientation of the sports teacher.